Success-score in professional soccer - Is there a sweet spot in the analysis of space and ball control? - Brinkjans, D.; Memmert, D.; Paul, Y.; Perl, J. (International Journal of Computer Science in Sport, 2023)
In contrast to simple performance indicators in the practical application of quantitative analysis in professional soccer, the inclusion of certain contextual elements can improve both the predictive quality and interpretability of these. Therefore, the Success-Score is intended to identify the factors relevant to success by linking ball control and space control. Position datasets from 14 games of the Bundesliga were used to calculate Success- Scores for several interval lengths for the penalty area and the 30-meter-zone. The relative goalscoring frequency above resp. below the 80th percentile, the rank correlation in terms of goals scored pursuant to the sorting of the Success-Score as well as possible distinctions in the Success-Score between two teams of different quality were examined. Results revealed that interval lengths and the area under investigation largely affect the resulting Success-Score and its distribution. The Success-Score applied to the 30-meter-zone seems preferable when analyzing goalscoring. Dependent on the target of analysis, methodological and theoretical considerations need to be balanced in a sweet spot of the interval length.